Remembering the Partisans and Yugoslav socialism - Pušnik, Maruša (Anthropological notebooks, 2017)
The aim of this study is to investigate the politics of memory and the transformations of memories of WWII and socialist Yugoslavia in the present-day Slovenia. I focus on the grass-roots, bottom-up memories that invade Slovenian public space, and I investigate 174 in-depth interviews with the middle- and old-age people. In this regard, the Slovenian nation is divided, positive memories of Yugoslav socialism's well-being and prosperity and the heroic Partisan struggle strongly clash with negative counter-memories of communist repression and Partisan inter-and post-war killings of Home Guards. The forced forgetting of WWII, the Partisans and Yugoslavia, which is promoted also by politically institutionalised top-down politics of memory, is created also in the popular, bottom-up memories of the informants. Such memory politics foster antitotalitarian and anti-communist discourses, creates Communism as the Other and produces Slovenian nationalism. Moreover, it blurs the WWII liberator-aggressor paradigm, when it suddenly becomes unclear who was liberator and who was aggressor during WWII, and it absolutely equates Hitler's Nazism with Communism.
Keywords: Druga svetovna vojna; World war II; Narodnoosvobodilna gibanja; National liberation movements; Reminiscing; Spominjanje; Slovenia; Slovenija; partizani; povojni poboji; politics; politika